Combustion aerosols from mineral oil industrial fires: Physicochemical characterization and toxicity in bronchial epithelial cells at the air-liquid interface - C. Méausoone; T. Rogez-Florent; C. Castilla; L. Chevalier; C. Bouzar; P. Cardinael; T. Legeard; S. Tisse; J. Yon; F. Portet-Koltalo; E. Varea; B. Patte-Rouland; et al. (Environmental Pollution, 2026)

Sarcoma metastasis: distinct biological principles beyond the carcinoma paradigm - Nadja Chevalier; Paul C. Nathan; Ivan Stamenkovic (Cancer and Metastasis Reviews, 2026)
Sarcomas are rare in adults but constitute a substantial fraction of pediatric malignancies and are characterized by a high propensity for hematogenous dissemination and poor outcomes once metastatic. Yet, most mechanistic understanding of metastasis derives from carcinomas and is frequently extrapolated to sarcomas despite major biological differences. This review synthesizes current evidence on sarcoma metastasis and highlights key knowledge gaps across the metastatic cascade. It frames sarcomas as malignancies often arising from mesenchymal stromal cells, whose intrinsic motility, plasticity, and stem-like features may predispose transformed cells to dissemination without requiring a classic epithelial-to-mesenchymal transition program. The concept of metastasis-initiating cells is discussed in the context of sarcoma cancer stem cell biology, clonal evolution, and epigenetic reprogramming, emphasizing that the relative genomic simplicity of certain pediatric sarcomas driven by recurrent fusion oncogenes may provide powerful models to dissect metastasis dependencies. The review examines how the sarcoma tumor microenvironment, often immunosuppressive and macrophage-rich, may shape invasion, intravasation, survival in circulation, extravasation, and organotropism, particularly the strong predilection for pulmonary metastasis. It summarizes emerging data on circulating tumor cells and complementary liquid biopsy approaches, while underscoring technical limitations caused by sarcoma heterogeneity and lack of robust markers. Finally, the review appraises current treatment limitations for metastatic sarcoma and argues that improved mechanistic resolution, especially of plasticity, epigenetic states, microenvironmental interactions, and dormancy, will be essential to identify actionable vulnerabilities and improve outcomes for patients with disseminated disease.

Histological and transcriptomic insights into gametogenesis in the flat oyster Ostrea edulis - Yanwen Lian; Anne-Sophie Le Port; Ann C. Andersen; Ricardo Gonzalez-Araya; Corentin Robert; Corentin Chevalier; Arnaud Uguen; Isabelle Boutet; Arnaud Tanguy (Aquaculture, 2026)

Paul Tapponnier, deciphering the Earth's crust deformation history in the rocks and landscapes - A. Replumaz; J.-P. Avouac; M.-L. Chevalier; Y. Klinger; C. Lasserre; P.H. Leloup; J. Liu-Zeng; G. Peltzer; J. van der Woerd; X. Xu (Tectonophysics, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

WITHDRAWN: Paul Tapponnier, deciphering the Earth's crust deformation history in the rocks and landscapes - A. Replumaz; J.-P. Avouac; M.-L. Chevalier; Y. Klinger; C. Lasserre; P.H. Leloup; J. Liu-Zeng; G. Peltzer; J. van der Woerd; X. Xiwei (Tectonophysics, 2026)

Using a comprehensive donor and host dataset to decipher the heritability and genetic architecture of pearl traits in the black-lipped oyster (Pinctada margaritifera) - L. Benestan; C. Massault; E. Vigouroux; O. Chevalier; D.B. Jones; D.R. Jerry; J. Le Luyer (Aquaculture, 2026)

No deformation propagation outward of the plateau across the Yalong Thrust Belt in Southeast Tibet - P. Pitard; A. Replumaz; P.H. Leloup; M.-L. Chevalier; S. Wang; M. Bai; X. Ou; M. Bernet; M. Balvay; E.R. Sobel; A. Vezinet; C. Gautheron; et al. (Tectonophysics, 2025)

P24-08 Chronic exposure to low-doses of maneb and manganese alters differentiation and lipid accumulation in hepatocytes in vitro - L. Chevalier; S. Pierre; M. Dufresne; M. Marceau; C. Pinteur; A. Corlu; B. Le Magueresse-Battistoni; P. Loyer (Toxicology Letters, 2025)

P08-12 Exposure to commercial copper-based nanopesticide reshapes chironomid-associated microbiota and alters host life history traits - L. Evariste; T. Moura; F. Chapeau; F. Candaudap; G. Le Roux; L. Chevalier; C. Larue; M. Barret; E. Pinelli; E. Houdeau; L. Gauthier; B. Lamas; et al. (Toxicology Letters, 2025)

Modelling the population dynamics of Rift Valley fever virus mosquito vectors in the western Mediterranean Basin - Alex Drouin; Thomas Balenghien; Benoit Durand; Carles Aranda; Amal Bennouna; Ali Bouattour; Said C Boubidi; Annamaria Conte; Sarah Delacour; Maria Goffredo; Oumnia Himmi; Grégory L'Ambert; et al. (Ecological Modelling, 2025)

Long-term impact of embryonic exposure to ethinylestradiol and clotrimazole on behavior and neuroplasticity in zebrafish (Danio rerio) - M. Blanc-Legendre; L. Guillot; L. Chevalier; C. Malleret; K. Le Menach; P. Pardon; H. Budzinski; F. Brion; S. Sire; P. Coumailleau; T.D. Charlier; E. Pellegrini; et al. (Environmental Toxicology and Pharmacology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P21-62 The copper-based nanopesticide Kocide 3000® worsens development of colitis in mice as a function of sex, and disrupts the intestinal barrier function in an enteroid-derived epithelial cell monolayer model from mouse gut organoids - E. Casale; Y. Malaisé; C. Cartier; E. Gaultier; L. Chevalier; T. You; S. Dupont; E. Houdeau; B. Lamas (Toxicology Letters, 2024)

Influence of the Rhone River intrusion on microplastic distribution in the Bay of Marseille - A. Alcaïno; L. Vidal; L. Licari; C. Paillès; S. Conrod; J. Dauvier; C. Chevalier; C. Pinazo; M. Grelaud; P. Ziveri (Regional Studies in Marine Science, 2024)

Water column distribution of zooplanktonic size classes derived from in-situ plankton profilers: Potential use to contextualize contaminant loads in plankton - B. Espinasse; M. Pagano; S.L. Basedow; C. Chevalier; D. Malengros; F. Carlotti (Marine Pollution Bulletin, 2023)

Genomic analysis of a parasite invasion: Colonization of the Americas by the blood fluke Schistosoma mansoni - Roy N. Platt; Winka Le Clec'h; Frédéric D. Chevalier; Marina McDew‐White; Philip T. LoVerde; Rafael Ramiro de Assis; Guilherme Oliveira; Safari Kinung'hi; Amadou Garba Djirmay; Michelle L. Steinauer; Anouk Gouvras; Muriel Rabone; et al. (Molecular Ecology, 2022)
Schistosoma mansoni , a snail‐borne, blood fluke that infects humans, was introduced into the Americas from Africa during the Trans‐Atlantic slave trade. As this parasite shows strong specificity to the snail intermediate host, we expected that adaptation to South American Biomphalaria spp. snails would result in population bottlenecks and strong signatures of selection. We scored 475,081 single nucleotide variants in 143 S. mansoni from the Americas (Brazil, Guadeloupe and Puerto Rico) and Africa (Cameroon, Niger, Senegal, Tanzania, and Uganda), and used these data to ask: (i) Was there a population bottleneck during colonization? (ii) Can we identify signatures of selection associated with colonization? (iii) What were the source populations for colonizing parasites? We found a 2.4‐ to 2.9‐fold reduction in diversity and much slower decay in linkage disequilibrium (LD) in parasites from East to West Africa. However, we observed similar nuclear diversity and LD in West Africa and Brazil, suggesting no strong bottlenecks and limited barriers to colonization. We identified five genome regions showing selection in the Americas, compared with three in West Africa and none in East Africa, which we speculate may reflect adaptation during colonization. Finally, we infer that unsampled populations from central African regions between Benin and Angola, with contributions from Niger, are probably the major source(s) for Brazilian S. mansoni . The absence of a bottleneck suggests that this is a rare case of a serendipitous invasion, where S. mansoni parasites were pre‐adapted to the Americas and able to establish with relative ease.

Application of the anatomical fiducials framework to a clinical dataset of patients with Parkinson’s disease - Mohamad Abbass; Greydon Gilmore; Alaa Taha; Ryan Chevalier; Magdalena Jach; Terry M. Peters; Ali R. Khan; Jonathan C. Lau (Brain Structure and Function, 2022)
Establishing spatial correspondence between subject and template images is necessary in neuroimaging research and clinical applications such as brain mapping and stereotactic neurosurgery. Our anatomical fiducial (AFID) framework has recently been validated to serve as a quantitative measure of image registration based on salient anatomical features. In this study, we sought to apply the AFIDs protocol to the clinic, focusing on structural magnetic resonance images obtained from patients with Parkinson’s disease (PD). We confirmed AFIDs could be placed to millimetric accuracy in the PD dataset with results comparable to those in normal control subjects. We evaluated subject-to-template registration using this framework by aligning the clinical scans to standard template space using a robust open preprocessing workflow. We found that registration errors measured using AFIDs were higher than previously reported, suggesting the need for optimization of image processing pipelines for clinical grade datasets. Finally, we examined the utility of using point-to-point distances between AFIDs as a morphometric biomarker of PD, finding evidence of reduced distances between AFIDs that circumscribe regions known to be affected in PD including the substantia nigra. Overall, we provide evidence that AFIDs can be successfully applied in a clinical setting and utilized to provide localized and quantitative measures of registration error. AFIDs provide clinicians and researchers with a common, open framework for quality control and validation of spatial correspondence and the location of anatomical structures, facilitating aggregation of imaging datasets and comparisons between various neurological conditions.

The hemolymph of Biomphalaria snail vectors of schistosomiasis supports a diverse microbiome - Frédéric D. Chevalier; Robbie Diaz; Marina McDew‐White; Timothy J. C. Anderson; Winka Le Clec'h (Environmental Microbiology, 2020)
Summary The microbiome ‐ the microorganism community that is found on or within an organism's body ‐ is increasingly recognized to shape many aspects of its host biology and is a key determinant of health and disease. Microbiomes modulate the capacity of insect disease vectors (mosquitoes, tsetse flies, sandflies) to transmit parasites and disease. We investigate the diversity and abundance of microorganisms within the hemolymph (i.e. blood) of Biomphalaria snails, the intermediate host for Schistosoma mansoni , using Illumina MiSeq sequencing of the bacterial 16S V4 rDNA. We sampled hemolymph from five snails from six different laboratory populations of B . glabrata and one population of B . alexandrina . We observed 279.84 ± 0.79 amplicon sequence variants per snail. There were significant differences in microbiome composition at the level of individual snails, snail populations and species. Snail microbiomes were dominated by Proteobacteria and Bacteroidetes while water microbiomes from snail tank were dominated by Actinobacteria. We investigated the absolute bacterial load using qPCR: hemolymph samples contained 2784 ± 339 bacteria/μl. We speculate that the microbiome may represent a critical, but unexplored intermediary in the snail–schistosome interaction as hemolymph is in very close contact with the parasite at each step of its development.

Persistent benthic communities in the extreme dynamic intertidal mudflats of the Amazonian coast: an overview of the Tanaidacea (Crustacea, Peracarida) - H. Thanh Nguyen; C. Dupuy; J. Jourde; C. Lefrançois; P.-Y. Pascal; A. Carpentier; J. Chevalier; P. Bocher (Marine Biodiversity, 2018)

A population of mitochondrion-rich cells in the pars recta of mouse kidney - M. S. Forbes; B. A. Thornhill; C. I. Galarreta; R. L. Chevalier (Cell and Tissue Research, 2016)

Erratum to: Influence of different GPS receiver antenna calibration models on geodetic positioning - Q. Baire; C. Bruyninx; J. Legrand; E. Pottiaux; W. Aerts; P. Defraigne; N. Bergeot; J. M. Chevalier (GPS Solutions, 2016)

Influence of different GPS receiver antenna calibration models on geodetic positioning - Q. Baire; C. Bruyninx; J. Legrand; E. Pottiaux; W. Aerts; P. Defraigne; N. Bergeot; J. M. Chevalier (GPS Solutions, 2014)

Air breathing in Magadi tilapia Alcolapia grahami , under normoxic and hyperoxic conditions, and the association with sunlight and reactive oxygen species - O. E. Johannsson; H. L. Bergman; C. M. Wood; P. Laurent; D. G. Kavembe; A. Bianchini; J. N. Maina; C. Chevalier; L. F. Bianchini; M. B. Papah; R. O. Ojoo (Journal of Fish Biology, 2014)
Observations of the Magadi tilapia Alcolapia grahami in hot, highly alkaline Lake Magadi revealed that they air breathe not only during hypoxia, as described previously, but also during normoxia and hyperoxia. Air breathing under these latter conditions occurred within distinct groupings of fish (pods) and involved only a small proportion of the population. Air breathing properties (duration and frequency) were quantified from video footage. Air breathing within the population followed a diel pattern with the maximum extent of pod formation occurring in early afternoon. High levels of reactive oxygen species ( ROS ) in the water may be an irritant that encourages the air‐breathing behaviour. The diel pattern of air breathing in the field and in experiments followed the diel pattern of ROS concentrations in the water which are amongst the highest reported in the literature (maximum daytime values of 2·53–8·10 µM H 2 O 2 ). Interlamellar cell masses ( ILCM ) occurred between the gill lamellae of fish from the lagoon with highest ROS and highest oxygen levels, while fish from a normoxic lagoon with one third the ROS had little or no ILCM . This is the first record of air breathing in a facultative air‐breathing fish in hyperoxic conditions and the first record of an ILCM in a cichlid species.

Trimetazidine demonstrated cardioprotective effects through mitochondrial pathway in a model of acute coronary ischemia - L. Dehina; F. Vaillant; A. Tabib; B. Bui-Xuan; Ph. Chevalier; N. Dizerens; C. Bui-Xuan; J. Descotes; V. Blanc-Guillemaud; L. Lerond; Q. Timour (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Evaluation of an immunochromatographic assay: Giardia-Strip® (Coris BioConcept) for detection of Giardia intestinalis in human fecal specimens - T. K. T. Nguyen; H. Kherouf; V. Blanc-Pattin; E. Allais; Y. Chevalier; A. Richez; C. Ramade; F. Peyron (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Complexity of the human whole saliva proteome - C. Hirtz; F. Chevalier; D. Centeno; J. C. Egea; M. Rossignol; N. Sommerer; Deville de Périère (Journal of Physiology and Biochemistry, 2005)

Fire and restoration of the largest urban forest of the world in Rio de Janeiro City, Brazil - D.M. Silva Matos; C. Junius F. Santos; D. de R. Chevalier (Urban Ecosystems, 2002)

Rapid molecular typing method for the reliable detection of Asiatic black truffle ( Tuber indicum ) in commercialized products: fruiting bodies and mycorrhizal seedlings - D. Mabru; C. Dupré; J. P. Douet; P. Leroy; C. Ravel; J. M. Ricard; B. Médina; M. Castroviejo; G. Chevalier (Mycorrhiza, 2001)

Intracellular vesicular trafficking in the gill epithelium of urea-excreting fish - P. Laurent; C. M. Wood; Y. Wang; S. F. Perry; K. M. Gilmour; P. Part; C. Chevalier; M. West; P. J. Walsh (Cell and Tissue Research, 2001)

A sensitive mapping strategy for monitoring the reproducibility of glycan processing in an HIV vaccine, RGP-160, expressed in a mammalian cell line - N.T. Tran; M. Taverna; A.H. Merry; M. Chevalier; G. Morgant; C. Valentin; D. Ferrier (Glycoconjugate Journal, 2000)

Critical power of knee extension exercises does not depend upon maximal strength - J. M. Le Chevalier; H. Vandewalle; C. Thépaut-Mathieu; M. Pujo; B. Le Natur; J. F. Stein (European Journal of Applied Physiology, 2000)

Suppression of apoptosis and induction of DNA synthesis in vitro by the phthalate plasticizers monoethylhexylphthalate (MEHP) and diisononylphthalate (DINP): a comparison of rat and human hepatocytes in vitro - Susan C. Hasmall; Neil H. James; Neil Macdonald; Douglas West; Stephan Chevalier; Sabina C. Cosulich; Ruth A. Roberts (Archives of Toxicology, 1999)

Socioeconomic status, social mobility and cancer occurrence during working life: a case–control study among French electricity and gas workers - B. Marshall; A. Chevalier; C. Garillon; M. Goldberg; F. Coing (Cancer Causes & Control, 1999)

Plasma serotonin level after 1 day of fluoxetine treatment: a biological predictor for antidepressant response? - J.-C. Alvarez; Nathalie Gluck; Alain Fallet; Anne Grégoire; Jean-François Chevalier; Charles Advenier; Odile Spreux-Varoquaux (Psychopharmacology, 1999)

Electromyogram as an indicator of neuromuscular fatigue during incremental exercise - C. Hanon; C. Thpaut-Mathieu; C. Hausswirth; J. M. Le Chevalier (European Journal of Applied Physiology, 1998)

Relation between lipid peroxidation and inflammation in the pulmonary toxicity of cadmium - Dino Manca; Anne C. Ricard; Huu Van Tra; Gaston Chevalier (Archives of Toxicology, 1994)

Impaired cortisol stress response in fish from environments polluted by PAHs, PCBs, and mercury - Alice Hontela; JosephB. Rasmussen; Cline Audet; Gaston Chevalier (Archives of Environmental Contamination and Toxicology, 1992)